Simmons, Betty. New Perlican Photograph of the 1993 Come Home Year Parade. - Barrett, Terra (1993)
A photograph of the 1993 New Perlican Come Home Year Parade. Alice Power is the blonde woman in the blue coat, pink shirt, and jeans; Winston Peddle is holding the flag/banner on the left; Gordon Penney is holding the other pole of the banner; and Betty Simmons is behind Winston in the white shirt. "Rockers" threw rocks at insulators on light poles.